The role of inseminators in the success of pregnancy outcome in Bali Cattle - Suteky Tatik; Dwatmadji Dwatmadji (E3S Web of Conferences, 2023)
The inseminators contribute an important role in the success of insemination therefore the research was conducted to evaluate the expertise and background of inseminators on the success of pregnancy outcomes. Seven inseminators from two districts were interviewed and related to their ability to do artificial insemination in Bali cattle in 2018. Reproductive data from January to December 2018 were analysed to determine their inseminator's performance from 2 districts (Kota Bengkulu and Bengkulu Tengah). One-way analysis of variance was tested to analyze the differences among inseminators on the result of AI pregnancy outcome, and a t-test was performed to determine whether the means pregnancy outcomes from two areas are different. Duncan's multiple range test was used to determine the significance of the difference between groups. The step-wise regression was applied to determine the strongest correlated variable. The result showed that conception rate (CR) and calving rate (CvR) differed significantly (P<0.05) among the inseminators, CR (81.30% vs 65.02) and CvR (76.68% vs 62.36%) also different between two districts. While the step-wise regression results showed that educational background, experience, age, and centre or unit for AI training become excluded variables while training (Assisted Reproductive Technology and pregnancy diagnosis) showed the strongest correlation with the pregnancy outcome. In conclusion pregnancy outcome differs between the two regencies and advanced training (Assisted Reproductive Technology and pregnancy diagnosis) showed the strongest correlation with the pregnancy outcome and the quality of the centre or unit for AI training is similar.